2017
DOI: 10.5812/iranjradiol.22019
|View full text |Cite
|
Sign up to set email alerts
|

Value of Real-Time and Strain Ratio Elastography in Differential Diagnosis of Graves’ Disease and Subacute and Hashimoto’s Thyroiditis

Abstract: Objectives: The main purpose of the present study was to determine the efficacy of real-time elastography (RTE) and strain elastography (STE) in the diagnosis of different thyroid diseases. We also aimed to calculate the cut-off points for the differential diagnosis of subacute thyroiditis (SAT), Graves' disease (GD), and Hashimoto's thyroiditis (HT), which have a similar B-mode sonographic appearance. Patients and Methods: A total of 24 patients with GD (10.9%), 94 patients with HT (42.7%), 20 patients with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In the present study, the mean elastography strain ratio was significantly high among patients with SAT which is explained by the fibrotic changes that markedly increased the stiffness of the gland tissue, while the strain ratio was significantly lower among patients with non-specific thyroiditis (p < 0.001). These results are in agreement with the results of Korkmaz et al study in Turkey on 24 patients with GD, 94 patients with HT, 20 patients with SAT, and 82 healthy controls and found that the mean elastography strain ratio was significantly higher in patients with SAT than the mean elastography strain ratio of patients with GD, HT, and healthy controls [2]. Another study carried out in Poland by Ruchala et al revealed that the sonoelastography is useful in the diagnosis and monitoring of SAT in addition to the differentiation between the variable types of diffuse thyroiditis [6].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the mean elastography strain ratio was significantly high among patients with SAT which is explained by the fibrotic changes that markedly increased the stiffness of the gland tissue, while the strain ratio was significantly lower among patients with non-specific thyroiditis (p < 0.001). These results are in agreement with the results of Korkmaz et al study in Turkey on 24 patients with GD, 94 patients with HT, 20 patients with SAT, and 82 healthy controls and found that the mean elastography strain ratio was significantly higher in patients with SAT than the mean elastography strain ratio of patients with GD, HT, and healthy controls [2]. Another study carried out in Poland by Ruchala et al revealed that the sonoelastography is useful in the diagnosis and monitoring of SAT in addition to the differentiation between the variable types of diffuse thyroiditis [6].…”
Section: Discussionsupporting
confidence: 92%
“…Ultrasound (US) can distinguish DTD (thyroiditis) from normal thyroid gland but it has a limited role in the characterization of the types of thyroiditis. Hence, more advanced radiological techniques have to be developed to give important useful information that are needed when planning management [2].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of sensitivity, specificity, and area under the curve (AUC), the cut-off points for strain elastography in patients with GD, HT, and SAT to the CG were 2.69 (sensitivity 92%, specificity 90%, AUC 0.983; 95% CI), 2.18 (sensitivity 100%, specificity 85%, AUC 0.898), and 5.54 (sensitivity 100%, specificity 100%, AUC 1.000; 95% CI), respectively. Strain ratios (SR) of all patients with HT and GD to SAT were cut off at 14.79 (sensitivity 80%, specificity 85%, AUC 0.869; 95% CI) ( 49 ).…”
Section: Discussionmentioning
confidence: 99%